Tuberculous Meningitis at the Department of Child Health Dr. Pirngadi Hospital, Medan - Margaretha Damanik; Sri Zamzah; Mardiana K. Djayusman; M. D. Marbun; Bistok Saing (Paediatrica Indonesiana, 1992)
Tuberculous meningitis was studied descriptively in 167 cases (1 .19%) of 14082 hospitalized patients at the Department of Child Health Dr. Pirngadi Hospital, Medan in a period of the years 1985 to 1989. The highest incidence was in the age group of under 3 years (46.11%) consisting 20. 78% of the stage I, 54.55% stage II, and 24.67% stage III. The youngest age was five months (2 cases) and the oldest was 14 years old (3 cases). The case fatality rate was 27.54%, they were 2.17% stage I, 32.61% stage II, and 65.22% stage III. Stage III showed higher mortality rate than stage I and II (p <0.001). The most frequent symptom was convulsion (43. 71%) followed by fever (33.53%) . Contact with patients who bad pulmonary tuberculosis were found in 56.28%. Positive tuberculin test was found in 17.96% and pulmonary radiological abnormalities in57.48%. The highest number oj cases (51.50%) was group with cerebrospinal fluid cell count of 101 - 500/mm Â· Cases which never got BCG immunization comprised 83.83%. The nutritional states on admission to the hospital were mild / moderate malnutrition in 67.07% and severe malnutrition in 32.93%.